Rachunek kosztów działań w szkołach wyższych - Kowalski, Michał Jerzy (Activity Based Costing in Colleges, 2006)
In the paper author ponders upon the possibilities of utilising the activity based costing by Polish colleges and universities. There was presented a draft of a university's expenditures calculation model, as well as threats its successive implementation process may bear. The below piece of work and the propositions herewith included constitute the results of the subject literature researches, consultations with cost experts at a major Polish technical university, inquiries made in academic environment and finally the author's own suggestions stemmed from his experience with Activity Based Costing systems.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1139, s. 205-215